THE ACADEMIC STRESS OF MALE AND FEMALE STUDENTS AT SMA N 1 PASIR PENYU IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Elni Yakub; Dwi Rahmayani, Tri Umari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The Covid-19 pandemic has made students learn through online learning, which is different from face-to-face learning. As a result, several problems might occurred due to this changing both for students and teachers. Online learning caused students to experience various academic problems, such as unstable internet connections, difficulties in understanding the materials, having more assignments, additional costs for buying internet packages, being unfamiliar with the online learning system, and increasing parents’ burden to help children in learning. Some of the problems mentioned above became a stressor for students in taking online learning. Based on the phenomenon reported by BK teachers at schools, male students were less disciplined in managing time during online learning. it was found that many male students skipped the class during online learning; many assignments were not submitted on time. As a result, their academic achievement decreased. On the other hand, female students focused more on the online learning and they were more likely to stay at home, so that it was easier for them to adapt to online learning compared to male students. The purpose of this study was to determine the differences in the level of academic stress of male and female students. The research samples were 155 students and the instrument in this study was an academic stress scale. This study obtained that the validity of the instruments was 0.3 and the reliability was 0.875. Then, the data were analyzed by independent sample T-test and descriptive analysis. The results showed that there were differences in the academic stress of male students and female students, in which the academic stress of the male students was higher than the academic stress of the female students.